A Modeling of Occupational Therapy Room Prototypes for Mental Disorders - Brigitha Watuseke (Journal of Artificial Intelligence in Architecture, 2023)
People with Mental Disorders (ODGJ) are less likely to recover completely. Still, there is a chance to recover and return to their normal activities Therapy that can make people with mental disorders carry out activities like ordinary people is occupational therapy. However, Indonesia still needs to offer an occupational therapy room design that can support the therapeutic process. This research developed an occupational therapy room modeling that can help the recovery process of people with a mental health condition with a neuroarchitecture approach through a 360o panoramic illustration. This research collects data from reliable sources regarding people with mental disorders, health workers, occupational therapy, neuroarchitecture, and theories regarding visual, texture, thermal, aroma, and audial. After that, space exploration is carried out based on ergonomics and considers the patient's senses. Based on the analysis results, it produces several rooms: outdoor areas, individual therapy rooms, group therapy rooms, entertainment rooms, work rooms, and toilets. The illustration of space modeling shows the use of interior elements such as the dominant color of the space, green and blue, the placement of high ceilings in the room that accommodates creative activities, and the low ceiling for the room accommodates privacy activities. In addition, space modeling also shows the type and placement of the furniture in every kind of space. Doctors or health experts can consider this modeling when making interior design guidelines for occupational therapy rooms.